Application of Results Based Management in Dental Public Health Of Prachuabkhirikhan Provincial Health Office, 2007 - จงกิตตินฤกร, ทินกร (Thai Dental Public Health Journal, 2008)
The aim of this research was to evaluate dental public health(DPH) performance following the application framework of results based management (RBM) in dental public health section of Prachuabkhirikhan provincial health office in the 2007 fiscal year. Data sources were documents related to management, reports on oral health services, provincial oral health survey and a questionnaire from dental personnel. The results showed that the RBM framework on DPH was composed of Vision, Mission, 4 critical success factors, 16 key performance indicators (KPIS) and target. After one year of implementation, there were 13 success KPIs (81.3%) that may be regarded as good level. The mean opinion score of dental personnel towards the KPIs was 3.68 that may be regarded as agreement level. In addition, there was statistically significant difference between the opinion level of dentist and dental nurses (p<0.05).